The subjective assessment of pain during the treatment of orthopaedic joint problems - J. Edeling (AOSIS, 1980)
A system is proposed whereby the pain syndrome may be numerically expressed. The system was developed for the assessment of conditions where pain was the dominant clinical feature and objective findings were minimal e.g. headaches derived from the cervical spine. A comprehensive subjective account of pain is recorded and three of the variables are numerically graded to reflect the severity of the total syndrome. An example is given in order to demonstrate the clinical use of the system.